2019
DOI: 10.3390/su11215903
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Simple Strategies to Improve Wellfield Management in Arid Regions: The Case Study of Wadi Al Arab Wellfield, Jordan

Abstract: Groundwater is the main source of drinking water supply in Jordan. Over the past 30 years, many wellfields have been drilled and expanded to cover increasing drinking water demand caused by natural population growth, development of life standards and as a result of the influx of refugees to Jordan. In particular, northern Jordan groundwater resources have been severely depleted. Therefore, water suppliers and utilities have been increasingly challenged to meet water demand and deliver water of adequate quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…We had a different response variable in comparison to the research made by Jeihoni et al ( 2015), but our results also showed the usefulness of ANN like the authors stated. Looking at the statistical indices, we found that the ANN has the highest efficiency which agrees with other findings (Khaki et al, 2015;Alizamir et al, 2017;Alqadi et al 2019;Sebghatiand Gholami, 2019;Meshram et al2020). We combined the results of ANN with Ordinary Kriging to predict groundwater condition map.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We had a different response variable in comparison to the research made by Jeihoni et al ( 2015), but our results also showed the usefulness of ANN like the authors stated. Looking at the statistical indices, we found that the ANN has the highest efficiency which agrees with other findings (Khaki et al, 2015;Alizamir et al, 2017;Alqadi et al 2019;Sebghatiand Gholami, 2019;Meshram et al2020). We combined the results of ANN with Ordinary Kriging to predict groundwater condition map.…”
Section: Discussionsupporting
confidence: 91%
“…Recent approaches in non-classical methods have also raised the bias in the application of spatial statistics for realization of spatial replacements (Jeihouni et al, 2015). The level of groundwater indicates groundwater availability, groundwater flow, and the substantial attribute of an aquifer (Nair and Sindhu, 2016;Alqadi et al, 2019). Several models have been used to evaluate groundwater quantity and quality in the world (Bodrud-Doza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Wadi Al Arab wellfield (Fig. 3c) provides around 40% of the drinking water supply of Irbid (Alqadi et al 2019), one of the biggest cities in Jordan with almost 1 million inhabitants (DoS 2019). When the wellfield was established in 1982, six out of nine wells of Wadi Al Arab wellfield were artesian; however, only a few years after production started, groundwater levels started to fall and spring flow in the area ceased almost completely (Subah and Hobler 2006).…”
Section: Wadi Al Arab Wellfield Case Studymentioning
confidence: 99%
“…e available freshwater is dominantly stored underground and accounts for approximately 96% of the total liquid freshwater on Earth [1]. Groundwater is a significant water source enabling the security of water and food and the key factor lifting the rural populations out of poverty over the world [2][3][4][5], especially in arid and semiarid regions with relative scarcity of surface water [6][7][8][9][10]. e availability of groundwater resources for the human community is limited not only by the water quantity but also by the hydrochemical quality [11,12].…”
Section: Introductionmentioning
confidence: 99%